Culture of Solea spp. - Dinis M.T.; Reis J. (Marine aquaculture finfish species diversification, 1995)
This paper deals with the broodstock management and larval rearing of Solea senegalensis Kaup obtained in a pilot-research project in Portugal since 1994. Solea senegalensis is a common species in the Southern European countries which is well adapted to warm climates and is exploited under extensive aquaculture in earth ponds in Portugal and Spain. After 7 months in captivity a wild broodstock spawned naturally and the spawning season lasts from March until June, at temperatures ranging from 16.5 plus minus 0.5 degrees C to 22 plus minus 1.0 degrees C and salinities from 30 per thousand to 35 per thousand. Eggs with 100 per cent fertilization presented viability ranging from 10 per cent to 90 per cent. Larvae were reared in 200 l fibreglass cylindroconical tanks and the newly hatched larvae had a total length of 2.66 plus minus 0.11 mm. As first feeding the larvae with a total length of 3.34 plus minus 0.08 mm were stocked at an initial density of 100 larvae/litre. Brachionus plicatilis was given as first feeding for larvae from day 3 to day 5 along with newly hatched Artemia nauplii from day 4 onwards. During the larval rearing the environmental conditions were: normal photo period, 35 per thousand salinity and a temperature of 18 degrees C. The benthic stage is achieved on day 19 when total length is 7.29 plus minus 0.09 mm and the larvae were then transferred to 200 litre flat bottomed fibreglass tanks. Survival rate at this stage ranged from 68.6 per cent to 87 per cent. Juvenile rearing was performed in the laboratory to day 38 where a total length of 16 plus minus 0.84 mm was achieved and the juveniles went to ongrowing areas in commercial fish farms. Larval feeding strategies as well as the weaning period will be discussed and the main problems will be identified. The ongrowing stage is still under progress, but the latest results indicators will be presented. An analysis of the possibilities of Solea senegalensis as a new species for aquaculture in the Mediterranean area will be discussed.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)